ADAPTIVE RELIGIOUS SKILLS: HOW TEACHER ACTUALIZE RUKHSAH IN TEACHING ISLAMIC PRAYER TO STUDENTS WITH DISABILITIES - Khairul Saleh; Muhamad Fajri; Sabran Sabran; Habib Anwar Alansori (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aims to analyze the strategies employed by Islamic Education teachers in teaching Shalat to students with special needs in Special Education Schools (SLBs) in Samarinda. Inclusive education for students with disabilities requires specific strategies that accommodate their cognitive and physical challenges in religious education, particularly in the practice of Shalat. A qualitative phenomenological approach was used, gathering data through observations, documentation, and interviews with teachers and school principals. The study found that individualized strategies, such as repetition, visual aids, peer tutoring, and structured programs like Shalat Dhuha, are essential in supporting students' participation in prayer. Key challenges identified include difficulties in memorizing prayers, limited teacher resources, and space constraints in prayer rooms. However, the study also highlighted the importance of community involvement, particularly parents, and the use of adaptive materials like videos and digital applications. This research contributes to the field of inclusive Islamic education by offering insights into effective teaching methods for students with disabilities. It recommends continued teacher training in adaptive pedagogies and the need for systemic changes to support inclusive education